Hypertensive crises - Graciela Florat García; Raymid García Fernández; Damaris Hernández Veliz; David García Barreto (ECIMED, 2014)
In order to characterize the patients with hypertensive crisis that attend the Emergency Department of the Institute of Cardiology and Cardiovascular Surgery an observational descriptive study was conducted among 128 consecutive patients with elevated readings and symptoms attributable to attack to a target organ. Of the 128 patients, 12 (9.3%) were emergencies and 86 (67%) were urgencies. The hypertensive crises were much more frequent in women than in men. 28 patients with crisis did not take any drug, 49 received only one drug and 17 had stopped the treatment through more than 3 mean excretory ducts. The patients went to the emergency department mostly in the morning and late in the afternoon. A signficant reduction of patients with crisis was observed during the evening. On Tuesdays and Wednesdays there were more crises than in the rest of the week. The commonest symptom on admission was precordial pain followed by headache. The most efficient drugs to obtain normotension were nifedipine and clonidine. Captopril was significantly less effective (p<0.05). Nifedipine had the relative risk of modifying the T wave of the EKG 12.3 times more (p<0.0001) than the rest of the drugs. Most of the patients with hypertensive crisis that receive medical attention at the Emergency Department of the Institute of Cardiology and Cardiovascular Surgery are urgencies that should be treated at the outpatient department. Emergencies appear with symptoms and signs attributable to an attack to a target organ and not to hypertension itself.